Stent malapposition generates stent thrombosis: Insights from a thrombosis model. (15th April 2022) - Ng, Jaryl Chen Koon; Lian, Shaoliang, Shawn; Zhong, Liang; Collet, Carlos; Foin, Nicolas; Ang, Hui Ying
Abstract: Background: Currently, there exists differing conclusions on the role of acute stent malapposition and its role in stent thrombosis (ST). The European Association of Percutaneous Cardiovascular Interventions (EAPCI) consensus recommends that acute malapposition <0.4 mm with longitudinal extension <1 mm need not be corrected since there is no clear correlation of malapposition with adverse clinical outcomes. However, malapposition was identified as the main mechanism of ST in the Bern and PESTO registries, and one of the three leading mechanism in the PRESTIGE study. Methods: In this study, a validated perfused benchtop thrombosis model was deployed to evaluate the role of both stent under-expansion (UE) and acute stent malapposition (MA) on thrombus formation in vitro in a controlled reproducible environment. Results: The results showed that UE alone did not result in acute thrombus formation, but UE together with MA did. The data suggested that a MA distance of 0.25 mm led to significant thrombus formation; and a positive correlation exists between the longitudinal extension of the MA and the thrombus volume formed. Conclusion: Experiments in this in vitro model demonstrated that platelets and a thrombosis cascade were activated and developed around large segments of malapposed stent. This was significantly more thrombus formation than in the under-expanded stent region. Highlights: Under-expansion alone did not result cause significant thrombosis in this in vitro model. Under-expansion with malapposition resulted in more thrombus formation. There is a positive correlation between length of malapposition and thrombus volume. The longer malapposition segments generated larger measured thrombus volume.